Advances on adaptive immune responses affected by infectious bursal disease virus in chicken - Zhang, Tao; Wang, Suyan; Liu, Yongzhen; Qi, Xiaole; Gao, Yulong (Frontiers in Immunology, 2024)
Infectious bursal disease (IBD) is an acute, highly infectious, and immunosuppressive disease caused by the infectious bursal disease virus (IBDV), which interferes with the immune system, causes hypoimmunity and seriously threatens the healthy development of the poultry industry. Adaptive immune response, an important defense line of host resistance to pathogen infection, is the host-specific immune response mainly mediated by T and B lymphocytes. As an important immunosuppressive pathogen in poultry, IBDV infection is closely related to the injury of the adaptive immune system. In this review, we focus on recent advances in adaptive immune response influenced by IBDV infection, especially the damage on immune organs, as well as the effect on humoral immune response and cellular immune response, hoping to provide a theoretical basis for further exploration of the molecular mechanism of immunosuppression induced by IBDV infection and the establishment of novel prevention and control measures for IBD.